The Joe Biden Way - Krames, Jeffrey A. (Ascent Audio, 2022)
Discover what sets leaders like President Biden apart from the rest In The Joe Biden Way: How to Become a Bold and Empathic Leader, bestselling author and leadership expert Jeffrey Krames provides listeners with leadership secrets gleaned from one of the most transformative and successful presidents in modern times: Joseph Robinette Biden, Jr. In this book, the author sets out seven lessons in inspiring leadership that have helped the forty-sixth president of the United States carry his powerful message to the White House and deliver it to hundreds of millions of people. You'll learn how to: lead with empathy and demonstrate you understand what your followers are experiencing; set a single priority and focus on it with laser precision; learn to execute on your goals and back your words with meaningful action; build on and cultivate your strengths and values; and lead diverse groups of people and inspire them to share a common goal. Perfect for executives, managers, and other business leaders, The Joe Biden Way is a must-have resource for anyone who strives to unlock the best in their followers and colleagues and discover what sets great leaders apart from the rest of the pack.